Reopening Oral Health Services during the COVID-19 Pandemic through a Knowledge Exchange Coalition. (July 2021) - McNally, M.; Rock, L.; Gillis, M.; Bryan, S.; Boyd, C.; Kraglund, F.; Cleghorn, B.
Background: The COVID-19 novel coronavirus closed oral health care in Nova Scotia (NS) Canada in March 2020. Preparing for a phased reopening, a knowledge exchange coalition (representing government, academia, hospitals, oral health professions, and regulators) developed return-to-work (RTW) guidelines detailing the augmentation of standard practices to ensure safety for patients, oral health care providers (OHPs), and the community. Using online surveys, this study explored the influence of the RTW guidelines and related education on registered NS OHPs during a phased return to work. Methods: Dissemination of R2W guidelines included website or email communiques and interdisciplinary education webinars that coincided with 2 RTW phases approved by the government. Aligned with each phase, all registered dentists, dental hygienists, and dental assistants were invited to complete an online survey to gauge the influence of the coalition-sponsored education and RTW guidelines, confidence, preparedness, and personal protective equipment use before and after the pandemic. Results: Three coalition-sponsored multidisciplinary webinars hosted 3541 attendees prior to RTW. The response to survey 1 was 41% (881/2156) and to survey 2 was 26% (571/2177) of registrants. Survey 1 (82%) and survey 2 (89%) respondents "agreed/strongly agreed" that R2W guidelines were a primary source for guiding return to practice, and most were confident with education received and had the skills needed to effectively treat patients during the COVID-19 pandemic. Confidence and preparedness improved in survey 2. Gowns/lab coat use for aerosol-generating procedures increased from 26% to 93%, and the use of full face shields rose from 6% to 93% during the pandemic. Conclusions: A multistakeholder coalition was effective in establishing and communicating comprehensive guidelines and web-based education to ensure unified reintegration of oral health services in NS during a pandemic. This multiorganizational cooperation lay the foundation for responses to subsequent waves of COVID-19 and may serve as an example for collaboratively responding to future public health threats in other settings. Knowledge Transfer Statement: The return-to-work strategy that was developed, disseminated, and assessed through this COVID-19 knowledge exchange coalition will benefit oral health practitioners, professional regulators, government policy makers, and researchers in future pandemic planning.